Basic culture of Sarawak: integration process toward UiTM Sarawak students from Peninsular Malaysia / Jackson Gerasi Henry ... [et al.] - Henry, Jackson Gerasi; Hamdin, Mohamad Syafie; Eqmal, Mozaidtul Asyariq (2010)
Malaysia has been considered to be a plural society. The plurality is because ofthe ethnic division coincide with religious and linguistic divisions enhanced by differences in customs and way oflife.(Wan Hashim, 1983). Sarawak, situated on the island of Borneo, is one of two Malaysian states along with Sabah comprising what is referred to as East Malaysia. Sarawak is the country’s largest state, occupying a land area of 124,449.51 square km; some 37.5% of the country’s total land mass. With a population of approximately 2.4m, Sarawak is the least densely populated of Malaysia’s 13 states. Home to 28 culturally distinct ethnic groups, it is also considered the country’s most ethnically diverse state, and is unique in that there is no single ethnic majority. The Iban, who are mostly agrarian and practice a form of Christianity mixed with traditional beliefs and rituals, comprise the largest ethnic group with approximately 30% ofthe population. The Chinese are next with some 27% ofthe population, followed by the Malays (23%). (Sarawak government portal). Sarawak is the largest state in Malaysia. It is separated to Peninsular Malaysia by the South China Sea. Sarawak haves 26 ethnicity with differ from cultures ofpeninsular Malaysia. Unity and National Integration are important to build a strong nation. Where there is an existence oftoleration and cooperation from this multiracial group, then it will lead to unity.